Moral agency within social structures and culture : a primer on critical realism for Christian ethics - Finn, Daniel K., 1947- (Washington, DC., Georgetown University press, 2020)
"Christian ethics has from the beginning been concerned with moral agency and culture, and Christian social ethics has acknowledged the power of social structures for the last 150 years. But ethics has yet to employ extensively the resources of that discipline that specializes in understanding structure and culture: sociology. Out of a concern to defend human freedom, Catholic social teaching has employed an individualistic approach that misdescribes the characteristics of social evil as little more than the sum of individual choices and proposes individual conversion as a remedy. This book presents a refined sociological understanding of social structures and culture: critical realist sociology. It briefly describes the roots of critical realism in the natural sciences, its understanding of social structure and culture, and how structure and culture have causal impact on human decisions - through freedom, not cancelling it. It makes clear how, in most cases, people "go along" with the restrictions and opportunities offered them but, when there is sufficient frustration with these, how decisions can transform both structure and culture. The analysis is then applied in more detail to provide needed illumination in three areas: the ecological crisis, economic life, and virtue ethics. The core claims of the volume, offering an explanatory account of moral-agency-amidst-structure-and-culture for use in social ethics, would be of great interest to all those working in the field, both Catholic and Protestant"--
Foreword / Margaret S. Archer -- How Critical Realism Can Help Christian Social Ethics / David Cloutier -- How Critical Realism Can Help Catholic Social Teaching / Theodora Hawksley, CJ -- What Is Critical Realism? / Daniel Finn -- Social Structures / Daniel Finn -- Culture / Matthew Shadle -- Critical Realism and Climate Change / David Cloutier -- Critical Realism and the Economy / Matthew Shadle -- Critical Realism, Virtue Ethics, and Moral Agency / Daniel Daly -- Further Reading -- Afterword / Lisa Sowle Cahill.
Includes bibliographical references and index.
Keywords: Christian ethics; Social ethics; Critical realism